THE EFFECT OF FINANCIAL LITERACY AND PRODUCT QUALITY ON THE INTEREST IN BUYING LIFE INSURANCE IN GEN Z MEDIATED BY GENDER AS A MODERATOR VARIABLE - Ita Nursita Sari; Putu Nina Madiawati; Mahir Pradana (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Abstract This study is motivated by the financial literacy of generation Z and also the quality of life insurance products in Indonesia which are moderated by gender in influencing a person's interest in buying life insurance in Indonesia. This study uses a quantitative method with a descriptive relationship approach. Determination of the sample in this study was carried out by calculating using the Bernoulli formula, with a total of 384 respondents. The data analysis technique used is the Structural Equation Model - Partial Least Square (SEM-PLS). The results of the study show that financial literacy (X1) and product quality (X2) do not have a significant effect on buying interest (Y) where the p-values of both variables are <0.05. Other findings also state that Gender (Z) does not significantly moderate financial literacy and product quality. The conclusion of this study is that the factors that make generation Z interested in buying insurance products are influenced by their perceptions of financial literacy and product quality. More specifically, the perception of product quality factors has a significant and positive influence on generation Z's interest in buying life insurance products in Indonesia. The findings show that of the two variables, product quality can be the strongest predictor in predicting generation Z's interest in purchasing life insurance products. Financial literacy cannot significantly predict generation Z's interest in purchasing insurance products. Keywords : financial literacy, product quality, gender, purchasing intention